Economic Valuation of Carbon Sink in PT Bio Farma (Persero) Forest Adoption Plot at Masigit Kareumbi Game Reserve - Yusuf Nugraha Andrian; Ratna Wingit; Nida Aulia Ulhaq (Prospect Publishing, 2023)
Forests have an important role in human life. Forests provide direct and indirect benefits. CO2 absorption and O2 production are some of the indirect benefits for human life. As a conservation forest, Masigit Kareumbi Game Reserve (TBMK) area is very important in CO2 absorption and O2 production. The TBMK Conservation Area has a fairly high level of social pressure which was the background for the emergence of the Forest Adoption program. Caring for and protecting the highly pressured TBMK area will be important for human life as the area acts as CO2 absorption, O2 production area, water catchment area, and clean water provider for the surrounding community. Bio Farma participates in caring for and protecting TBMK forests by participating in the Forest Adoption program. Wali Pohon PT Bio Farma (Persero) has carbon stocks of 134.095 tons, a CO2 absorption value of 418.464 tons/hectare/year, and an O2 production value of 358.0.33 tons/hectare/year. If evaluated, the PT Bio Farma (Persero) Wali Pohon plot has a carbon absorption value of IDR 28,318,422 (twenty-eight million three hundred eighteen thousand four hundred and twenty-two rupiah).